Vegetation structure, natural regeneration and management of Parroha community forest in Rupandehi district, Nepal - Acharya, Rajendra; Shrestha, Babat Babu (Scientific World, 2011)
Understanding vegetation structure and regeneration in community forests in important for management planning. The present work was done during September to October 2005. The information on forest management practices was collected by Participatory Rural Appraisal (PRA) which included field observation, interviews and focus group discussion. A total of 125 plant species belonging to 55 families with 36 tree species, 50 shrubs and 39 herbs were recorded from the 0.7 ha sampling area. The total tree density and basal area at South-East (SE) facing slope was 595 pl/ha and 29.68 m²/ha, respectively, where Terminalia alata was the most dominant with highest importance value index (IVI). On the other hand, total tree density and basal area was 453 pl/ha and 41.78 m²/ha, respectively, at South-West (SW) facing slope, where Shorea robusta was the most dominant with the highest IVI. Total shrub/sapling density was 4708 pl/ha at SE slope and 4137 pl/ha at SW slope. Similarly, total herb/seedling density was 10.86 pl/m² at SE slope and 9.79 pl/m² at SW slope. The total number of tree species (S) in tree stage was higher at SE slope than at SW slope and the number of species in shrub layer was higher at SE slope than at SW slope. The two slopes had nearly equal number of species in herbaceous layer. Higher species diversity (H) of different lifeforms was found at SW slope. The SW slope had higher species evenness (J) and Simpson’s index of dominance (C) for all life forms than at SE slope. High similarity index for all tree, shrub/sapling and herb/seedling layers (63.63%, 84.61% and 77.10% respectively) were found between two sites. Alpha (α) diversity for shrub layer was higher at SE slope whereas beta (β) diversity for tree layer was higher at SW slope than at SE slope. Regeneration of Shorea robusta and Terminalia alata was continuous because density increased from tree, sapling to seedlings with a typical reverse J shaped size class diagram at both slope. But regeneration of S. robusta at SW slope was sporadic. The reccurence of forest fire during summer season has appeared as a major problem for the management of forest. The active participation of the local people in forest conservation activities can be effective for sustainable management of forest. Keywords: Community forestry; Vegetation; Regeneration; Size class diagram; Shorea robusta; Terminalia alata. DOI: http://dx.doi.org/10.3126/sw.v9i9.5523 SW 2011; 9(9): 70-81